Recruiting and Job Search Technologies in the Age of Internet - Sergey Roshchin; Sergey Solntsev; Dmitry Vasilyev (Foresight and STI Governance, 2017)
The article considers recruiting via the internet as an organizational innovation in Russian companies. Using data from a survey of employers and RLMS-HSE, we measured the scale of internet-use by employers for recruiting and by employees for the job search, and the factors influencing them. In general, the characteristics of employees and workplaces were in line with one another. Amid companies, internet use was more common in the retail sector, among privately owned and financially successful firms. The internet was more actively used by workers with higher or specialized education from big cities. Internet search complements other search channels and has become the second most popular channel after searching for work through relatives and friends.